A Crisis by and for Capital. Issue 2 (2nd July 2020) - Ferdosi, Mohammad
Abstract : In the industrial world, the post-crisis years were marked by systematic attempts by governments to retrench the laws, programmes and institutions that provided the working class with some degree of protection from the inherent instabilities and excesses of capitalist development. These corporate inspired and state-led attacks on workplace and labour market rights were largely a continuation of earlier decades of neoliberal retrenchment, when capital gained the upper hand in the class struggle and began to reverse what labour had won in the postwar period.